Current Status and Future of Turkey in Research and Development Activities: A General Review and Recommendations - (:unkn) unknown (MALIYE BAKANLIGI, 2017)
Turkey has made regulations mainly including financial incentives and set specific targets in order to enhance R&D activities in the country and ensure the specific attention of private sector in this field and reach a particular level in R&D activities. For this purpose, public R&D resources were increased and comprehensive incentive policies were developed for R&D activities of private sector. However, the policies have not produced desired outcomes yet. The main aim of the present study is to analyse how policies to enhance R&D activities have contributed to established targets by means of data. Current status of Turkey in the world is examined by means of R&D data and policies to reach future R&D goals are analyzed through the decisions of Supreme Council of Science and Technology. Additionally, new policies that may serve to further improvement of R&D activities in Turkey are mentioned.
Keywords: R&D Activities; International R&D Activities; R&D Policies in Turkey